Effect of rituximab in patients with leucine-rich, glioma-inactivated 1 antibody-associated encephalopathy. - Irani, SR; Gelfand, J; Bettcher, B; Singhal, N; Geschwind, MD (2014)
IMPORTANCE: This observational study describes the efficacy and safety of rituximab in 5 patients with voltage-gated potassium channel (VGKC)-complex/leucine-rich, glioma-inactivated 1 (LGI1) antibody-associated encephalopathy. Rituximab is a monoclonal antibody that targets CD20 and is used to treat other neurologic and nonneurologic diseases. OBSERVATIONS: This case series reports sequential seizure frequencies, modified Rankin Scale scores, and VGKC-complex antibody titers in 5 adult patients (median age, 65 years; range, 48-73 years) treated with rituximab. Median time from symptom onset to rituximab initiation was 414 days (range, 312-851 days). One patient showed a rapid clinical improvement after treatment with rituximab alone and experienced a rituximab-responsive clinical relapse. Another showed possible improvement on neuropsychometric memory indexes after rituximab therapy. In contrast, all patients showed robust responses to treatment with glucocorticoids, intravenous immunoglobulins, and/or plasma exchange at some point in their illness. Treatment with glucocorticoids-less so with intravenous immunoglobulins and plasma exchange-was associated with the most marked reductions in VGKC-complex antibodies. The only patient who did not receive glucocorticoids showed the poorest clinical and serologic responses. CONCLUSIONS AND RELEVANCE: Rituximab was well tolerated in this predominantly older adult patient population and may be an effective option for some patients with LGI1 antibody-associated encephalopathy. Glucocorticoid therapy appears particularly efficacious. Earlier rituximab administration and randomized trials are required to formally assess efficacy.